ANALYSIS ON LABORERS INCOME IN MALANG CITY CASE STUDY: E-COMMERCE - Pratama, Dewa Ageng; A, Nursiswati; Sulistiyanti, Sulistiyanti (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The development of technology, especially the internet, has made great progress for society, It is supported with the government regulation of work from home (WFH) in pandemic time, which has increased the number of internet users. Trading is no exception. This forced the entire workforce with various backgrounds to conduct online-trading activities. The research objective was to determine the effect of digital trade (e-commerce) on laborers’ income in Malang City. Researchers used a quantitative descriptive method to describe the workforce in Malang City. This research was a quantitative study using cross-sectional data collected by SAKERNAS in 2020 and it was estimated by using the multiple linear regression method. The characteristics of the workforce used in this study were education, the working age range of 15-64 years, male or female sex, and married status. The researcher has the implication that if the effect of e-commerce on labor income was very high, this can be an alternative for a new job.